THE SIGNIFICANCE OF THE FINANCIAL SERVICES AUTHORITY’S APPROVAL ON THE SALE AND PURCHASE OF A LIMITED LIABILITY RURAL BANK’S SHARES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This research will discuss the process of buying and selling shares of Rural Banks in the form of Limited Liability Companies According to applicable regulations and the significant of the Financial Services Authority’s approval on the sale and purchase of shares of Rural Bank. The author uses the theory of law as a grand theory, banking law theory as a middle theory and certainty of law as applied theory in this thesis. The research method used is normative juridical supported by empirical, namely by examining the rules relating to the sale and purchase of shares of Rural Banks and field research in the form of interviews conducted at the Financial Services Authority.The sale and purchase of shares of a Rural Bank conducted prior to the approval of new shareholders / new controlling shareholders, causes the new shareholders to transfer their shares and not obtain the rights as shareholders. The general meeting of shareholders that have been made to sell and determine the buyers of shares must be canceled if after going through the fit and proper test, the prospective new shareholders get the title of Unapproved. The approval of the Financial Services Authority has become significant in share sale and purchase transactions which has caused new shareholders / new controlling shareholders.